Cross-Platform Political Communication by Target and the New Season of Politics in Italy - Iazzetta, Ferdinando; Punziano, Gabriella; De Falco, Ciro Clemente; Trezza, Domenico (Italian Sociological Review, 2024)
The results of the 2018 national elections, together with the socio-demographic heterogeneity of the main social platforms, make it interesting to understand if and how social categories have been mentioned or incorporated into the 2022’s national electoral campaign in Italy. This contribution aims to analyze the multi-platform communication of the main political candidates from various coalitions and parties to investigate whether they based their media campaign on specific social categories and issues, and whether this effort had the electoral impact it deserved. Empirical evidence shows that only some candidates have focused their attention on specific social categories without taking into account the diverse audiences of the platforms.